Impact of hydrothermal activity on marine barium isotope composition: a case study from the Southwestern Indian Ocean - Zhao, Chunxiao; Li, Li; Li, Jiejun; Xie, Ruifang C.; Wang, Xiaojing; Shi, Xuefa (Frontiers in Marine Science, 2025)
The cycling of barium (Ba) is closely linked to marine biogeochemical processes. Barium and its isotopes are commonly used as tracers for marine productivity, seawater alkalinity, and ocean circulation. Mid-ocean ridge hydrothermal systems significantly impact marine chemistry, acting as key sources of trace elements in deep seawater. However, the overall contribution of hydrothermal Ba to the global Ba cycle remains poorly quantified, and studies on hydrothermal Ba isotopes are limited, hindering a comprehensive understanding of the marine Ba cycle. This study investigated the concentration of dissolved Ba and other elements, along with Ba isotope composition (δ138Ba), in the hydrothermal influenced water and sediment samples collected near the Longqi and Tiancheng vents in the southwestern Indian Ocean. This constitutes the first such investigation in this region. The vertical profiles of dissolved Ba and its isotope compositions mirrored each other in the southwestern Indian Ocean, consistent with prior observations in other ocean basins. For near-field water samples, Ba isotope compositions (-0.10‰ to 0.05‰) are significantly lower than background seawater ( 0.29‰). In addition, Hydrothermal sediments exhibited Ba isotopic values (-0.16‰ to 0.01‰) markedly lower than background sediments (0.01‰ to 0.14‰). The depleted δ138Ba values of near-field water samples indicate preferential removal of lighter Ba isotopes during the mixing of hydrothermal fluids with seawater. Consequently, precipitated particles acquire lighter Ba isotope signatures, explaining the low values in hydrothermal sediments. This demonstrates that sediments effectively capture and preserve hydrothermal Ba signals. Collectively, these findings provide new insights into hydrothermal influences on the marine Ba cycle.